2020
DOI: 10.1108/oir-12-2019-0372
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of graphic-based tag clouds: theory and experimental evaluation for information search

Abstract: PurposeGraphic-based tag clouds aim to visually represent tag content and tag structure, and then to better represent tagged information for later search. However, few studies have clarified the features among varied visualization approaches involved in graphic-based tag clouds and compared them for the purpose of information search.Design/methodology/approa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 58 publications
(61 reference statements)
0
1
0
Order By: Relevance
“…Prior studies (Ruan et al , 2020; Ahmed et al , 2012; Stout et al , 2001) have posited that the navigation structure of the online platforms should provide more opportunities to create a more interactive environment for the users. Further, it is suggested that graphics-based tagged content on the websites provides a better “search option” during searching information (Ma and Ma, 2020). Eventually, in the current study, the navigation structure is explored as a significant indicator from the user perspective that demonstrated its practical feasibility, especially for mental health-related websites.…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies (Ruan et al , 2020; Ahmed et al , 2012; Stout et al , 2001) have posited that the navigation structure of the online platforms should provide more opportunities to create a more interactive environment for the users. Further, it is suggested that graphics-based tagged content on the websites provides a better “search option” during searching information (Ma and Ma, 2020). Eventually, in the current study, the navigation structure is explored as a significant indicator from the user perspective that demonstrated its practical feasibility, especially for mental health-related websites.…”
Section: Discussionmentioning
confidence: 99%